Analisis Kepercayaan Diri Siswa SMP Kelas IX Pada Materi Bangun Ruang Berbantuan Aplikasi Geogebra - Neng Cucu; Sri Rizqi; Wahyu Setiawan (Journal on Education, 2020)
This study aims to analyze the confidence of junior high school students of class IX on geogebra application assisted material. The research method uses a qualitative descriptive study with the population of all middle school students in West Bandung regency. The sample used was class IX students of SMPN 3 Cihampelas as many as 36 students on space building material. The instrument used was a student confidence scale with 14 statements that had positive and negative responses about learning using the geogebra application. This scale is used to look for responses from respondents on the confidence of junior high school students on building materials with learning assisted by geogebra applications. With the results of the questionnaire answered by students showed that students' confidence in learning materials to build space with geogebra application media showed positive results with an average response showed a strong category with the acquisition of a percentage of 68.25%. The average was obtained from the data of each indicator Student confidence.